PENGARUH RETAIL MIX TERHADAP IMPULSE BUYING PADA HYPERMARKET DI KABUPATEN BADUNG - Dewi, Kadek Kumala; Ekawati, Ni Wayan (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect that mix retail locations, merchandising, pricing, promotions, the atmosphere in the stores, and retail service to impulse buying at hypermarket in Badung. The location of this research carried out at hypermarket in Badung, namely Mal Lippo Mall Bali Galeria and Kuta. The population in this study is every visitor who do impulse buying at the hypermarket in Badung is the hypermarket in Mall Bali Galeria and hypermarkets in Lippo Mall Kuta. Respondents who were sampled as many as 224 people and conducted with a purposive sampling technique. This study used multiple linear regression analysis. The results showed the location, merchandising, pricing, promotions, the atmosphere in the stores, and retail service significant positive effect on impulse buying, it means the location, merchandising, pricing, promotions, the atmosphere in the stores, and retail service encourage behavior impulse buying consumer hypermarket in Badung regency.
Keywords: retail mix, impulse buying, dan hypermarket